Impact of sustainability and nutritional messaging on Italian consumers' purchase intent of cereal bars made with brewery spent grains. Issue 2 (18th January 2021) - Stelick, Alina; Sogari, Giovanni; Rodolfi, Margherita; Dando, Robin; Paciulli, Maria
Abstract : Abstract: This work focuses on the reuse of brewery spent grains (BSGs), the most abundant by‐product of the beer industry, today mainly used as animal feed. BSGs are rich in fibers and proteins as well as phenolic compounds, all of which are beneficial for human nutrition. Cereal bars containing 12% BSG were formulated and characterized instrumentally. Moreover, 159 panelists representative of young Italian consumers evaluated the bars in a central location test, along with a commercial cereal bar. Products were first evaluated blind, and then in an informed condition where additional product‐specific nutritional and sustainability information was revealed, thus the purchase intent was determined. While the control product outperformed the BSG bar in most of the hedonic and sensory measures, the BSG sample was perceived as "natural/made with natural ingredients" by a significantly higher number of panelists (49%) compared to the control (30%). Additionally, even in the lower performing formulation, a significant positive effect on purchase intent was observed when providing either nutrition (fiber content) or sustainability (use of upcycled ingredients) information. The acceptable price range for the BSG and the commercial bar was very similar, whereas the optimal pricing point for the BSG was lower than the control. For the BSG product, sustainability information had significantly higher impact on purchase intent than nutrition‐based information. Results highlight the importance of understanding consumer attitudes toward upcycling and the use of byproducts as ingredients in new food formulations. Practical Application: Results show how providing information on product nutrition and sustainability can increase purchase intent in the context of a cereal bar containing upcycled ingredients. The findings of this study can help food and consumer researchers to develop acceptable products that include BSG as an ingredient, potentially replacing other cereals in the recipe. The use of this brewery by‐product could add value to the beer supply chain and to the final product as well, being also aligned with the current market trend of sustainability and functional health benefits.